Luminescence and scintillation properties of Cs3ZnCl5 and Cs3ZnCl5 (Eu) single crystals - Oleg Yurchenko; Olexandr Rebrov; Victor Cherginets; Ianina Boyarintseva; Tetyana Rebrova; Tamara Ponomarenko; Oleksiy Lebedinskiy; Olga Zelenskaya (Вісник Харківського національного університету: Серія xімія)
This paper reports the results on obtaining and investigation of functional parameters of Cs3ZnCl5 crystals grown using Bridgman method from the melts of 3CsCl-2ZnCl2 and 3CsCl-1.995ZnCl2-0.005 EuCl2 compositions. The study of photoluminescence spectra obtained at 237 nm excitation shows the presence of the following emission bands: one at 325 nm caused by the defects or impurities, slightly pronounced band at ca. 450 nm caused by the presence of Eu2+ ions and a series of bands in 590÷700 nm range due to the presence of Eu3+ in the crystals. The presence of said Eu ions is confirmed by the luminescent studies with the use of excitation at wavelengths proper to Eu2+ (340 nm) and Eu3+ (465 nm). X-ray luminescence spectra include the bands with maxima of 235 nm and 285 nm which are caused by the core-valence luminescence, the band with the maximum at 320 nm caused by the defects and impurities and two bands with the maxima at 400 and 520 nm which nature is not clear (probably, it can be connected with the presence of Eu3+ in the samples). The study of light yield performed at the light collection time of 2 μs showed that for all the samples its value is ca. 6% vs. BGO crystal (Bi4Ge3O12) and the form of the pulse-height spectra for the crystals grown from both melts practically coincide. This leads to the conclusion that the transfer of excitation from the matrix to Eu2+ ions is absent and, according to the photoluminescence studies it can be assumed that Eu2+ exists in the said crystals as inclusions of CsCl:Eu2+ solid solution.